Pengaruh Pemanasan Awal Udara Terhadap Performa Crossdraft Gasifier Dengan Bahan Bakar Sekam Padi - Santosa, Giri (2016)
Crossdraft gasifier is a tool that can be used to convert biomass energy from rice husks into other, more useful energy. Therefore, the purpose of this study was to investigate the effect of air to preheat the combustion temperature, water temperature, effective flame and thermal efficiency of the furnace to obtain optimal performance of crossdraft gasifier This study uses a cross-draft gasifier is used as a stove with a diameter in the reactor of 170 mm and a height of the reactor 845 mm as well as the use of insulating powder brick in the wall of the reactor to boil 1 liter of water using fuel 1 kg of rice husk and air as an agent, do a variation on agent in the form of variations in the initial temperature of air, among others, the initial temperature of normal air (32 ° C), 50 ° C and 80 ° C at the same air flow velocity is 5.5 m / s are then measured combustion temperature, water temperature and effective flame The results showed the beginning of the air temperature variation affects the combustion temperature, water temperature, effective flame and furnace thermal efficiencies generated. At the beginning of the normal air temperature (32 ° C) the highest combustion temperature 874.3 ° C, while boiling water for 3 minutes, the flame effective for 12.5 minutes and the thermal efficiency of the furnace at 6:19%. At the beginning of the air temperature 50 ° C the highest combustion temperature of 913 ° C, while boiling water for 3 minutes, 11.5 minutes effectively during the flame and furnace thermal efficiency of 7,552%. At the beginning of the air temperature 80 ° C the highest combustion temperature is 940.66 ° C, while boiling water for 3 minutes, effective flame for 11 minutes and the furnace thermal efficiency of 5.61%.